Considering non‐bladder aetiologies of overactive bladder: a functional neuroimaging study. (8th March 2021) - Walter, Matthias; Leitner, Lorenz; Betschart, Cornelia; Engeler, Daniel S.; Freund, Patrick; Kessler, Thomas M.; Kollias, Spyros; Liechti, Martina D.; Scheiner, David A.; Michels, Lars; Mehnert, Ulrich
Abstract : Objectives: To better understand the neuropathophysiology of overactive bladder (OAB) in women by characterising supraspinal activity in response to bladder distention and cold stimulation. Subjects/Patients and Methods: We recruited 24 female participants, 12 with OAB (median [interquartile range, IQR] age 40 [32–42] years) and 12 healthy controls (HCs) without lower urinary tract (LUT) symptoms (median [IQR] age 34 [28–44] years), and assessed LUT and cognitive function through neuro‐urological examination, 3‐day bladder diary, urodynamic investigation, and questionnaires. Functional magnetic resonance (MR) imaging using a 3‐T scanner was performed in all participants during automated, repetitive bladder filling and draining (block design) with 100 mL body temperature (37 °C) saline using a MR‐compatible and MR‐synchronised infusion–drainage device until strong desire to void (HIGH‐FILLING/DRAINING) and bladder filling with cold saline (4 °C, i.e. COLD). Whole‐brain and region‐of‐interest analyses were conducted using Statistical Parametric Mapping, version 12. Results: Significant between‐group differences were found for 3‐day bladder diary variables (i.e. voiding frequency/24 h, P < 0.001; voided volume/void, P = 0.04; and urinary incontinence [UI] episodes/24 h, P = 0.007), questionnaire scores (International Consultation on Incontinence Questionnaire‐Female LUT symptoms [overall, filling, and UI scores, all P < 0.001]; the Overactive Bladder Questionnaire short form [symptoms and quality‐of‐life scores, both P < 0.001]; the Hospital Anxiety and Depression Scale [anxiety P = 0.004 and depression P = 0.003 scores]), as well as urodynamic variables (strong desire to void, P = 0.02; maximum cystometric capacity, P = 0.007; and presence of detrusor overactivity, P = 0.002). Age, weight and cognitive function (i.e. Mini‐Mental State Examination, P = 1.0) were similar between groups ( P > 0.05). In patients with OAB, the HIGH task elicited activity in the superior temporal gyrus, ventrolateral prefrontal cortex (VLPFC), and mid‐cingulate cortex; and the COLD task elicited activity in the VLPFC, cerebellum, and basal ganglia. Compared to HCs, patients with OAB showed significantly stronger cerebellar activity during HIGH‐FILLING and significantly less activity in the insula and VLPFC during HIGH‐DRAINING. Conclusions: The present findings suggest a sensory processing and modulation deficiency in our OAB group, probably as part of their underlying pathophysiology, as they lacked activity in essential sensory processing areas, such as the insula. Instead, accessory areas, such as the cerebellum, showed significantly stronger activation compared to HCs, presumably supporting pelvic‐floor motor activity to prevent UI. The novel findings of the present study provide physiological evidence of the necessity to consider non‐bladder aetiologies of bladder symptoms.